Reduced spike specific T-cell responses in COVID-19 vaccinated subjects undergoing SARS-CoV-2 breakthrough infection - Varchetta, Stefania; Golfetto, Federica Sole; Bono, Patrizia; Callegaro, Annapaola; Fabbris, Tanya; Favalli, Andrea; Crosti, Mariacristina; De Feo, Tullia Maria; Iannotti, Nathalie; Bozzi, Giorgio; Castelli, Valeria; Mariani, Bianca; et al. (Frontiers in Immunology, 2025)
IntroductionT-cell responses to SARS-CoV-2 remain largely preserved across variants despite waning neutralizing antibodies. However, T-cell immunity may vary with the host’s immune status, and data on T-cell responses in post-vaccine infections (PVI) are limited.MethodsWe assessed Spike-specific T-cell responses in 32 vaccinated individuals, 16 of whom experienced PVI. Immune responses were evaluated at three time points: 1 month after the second vaccine dose (T1), 1 month after the booster dose (T2), and, in the PVI group, 1–3 months after the first positive nasal swab (T3). Additionally, we evaluated anti-spike antibody levels, T-cell exhaustion markers, and natural killer cell subsets, focusing on memory-like CD57+ NKG2C+ cells.ResultsSubjects who developed PVI exhibited significantly reduced Spike-specific CD4 T-cell responses following the booster dose compared to vaccinated individuals who remained uninfected. This was accompanied by increased frequencies of LAG-3+ CD4+ and CD8+ T-cells. A positive correlation was observed between AIM+ CD4+ T-cells and NKG2C+ NK cells at T2 in PVI subjects. Following natural infection, T-cell responses were enhanced and associated with an expansion of NKG2C+ NK cells.ConclusionsIndividuals experiencing PVI displayed impaired booster-induced CD4+ T-cell responses and increased expression of the immune checkpoint LAG-3. Natural infection restored and enhanced cellular immunity, particularly through the expansion of Spike-specific T-cells and memory NK cell populations. This study identifies an immune profile characterized by low spike-specific responses, which are associated with an increased susceptibility to breakthrough infections.